Penilaian Awal Potensi Kerusakan Danau Anggi Giji dan Danau Anggi Gida, Kabupaten Pegunungan Arfak, Papua Barat - Thomas Frans Pattiasina; Giri Suryanta; Wakhidah Heny Suryaningsih; Marthin Matulessy (Musamus Fisheries and Marine Journal, 2021)
The potential of natural resources and the high aesthetic value of Lake Anggi Giji and Lake Anggi Gida in the Arfak Mountains Regency, West Papua are capital for regional development. However, development activities in the lake area and its surroundings can cause damage to the lake. This study aims to identify and analyze the potential damage to Lake Anggi Giji and Anggi Gida in Arfak Mountains District, West Papua. The method applied is descriptive method. Assessment of potential damage is based on lake damage assessment parameters in accordance with Dirjen PDASHL Regulation No. P.4/PDASHL/SET/KUM.1/3/2019 concerning Lake Damage Control. Data were collected through observation, unstructured interviews, documentation and literature search. The data analysis was carried out by comparing the real conditions of the lake with the criteria for damage to the lake and with the relevant theories. To support the analysis, data processing of Landsat 8 OLI satellite imagery and high-resolution satellite imagery from Google Earth is carried out. The results of the initial damage assessment generally show that Lake Anggi Giji and Lake Anggi Gida are in good condition. However, it is necessary to make efforts to prevent damage to the lake to ensure the sustainability of the ecosystem services of the two lakes.